The Rise of Standard I (< Me Ich): A Contribution to the Study of Functional Change in English - Wełna, Jerzy (Studia Anglica Posnaniensia, 2015)
In its post-Norman Conquest development the Old English first person personal pronoun ic underwent transformations which, following the loss of the consonant, finally yielded the contemporary capitalised form I, contrasting with other Germanic languages, which retain a velar sound in the corresponding pronoun. The rather complex change of ich to I involves a loss of the final velar/palatal consonant, lengthening of the original short vowel, and capitalisation of the pronoun. It is argued here that the use of the capital letter was a consequence of vowel lengthening subsequent to the loss of the consonant. This seems to be confirmed by the observation that forms retaining a consonant are extremely rarely capitalised. The data adduced in the present paper will help verify as precisely as possible the distribution of the forms of that pronoun in Middle English dialects in order to determine to what extent the changes were functionally interdependent. The evidence comes from the Innsbruck Corpus of Middle English Prose.